2019
DOI: 10.1007/s00415-019-09625-1
|View full text |Cite
|
Sign up to set email alerts
|

Exit strategies for “needle fatigue” in multiple sclerosis: a propensity score-matched comparison study

Abstract: Check the metadata sheet to make sure that the header information, especially author names and the corresponding affiliations are correctly shown. • Check the questions that may have arisen during copy editing and insert your answers/ corrections. • Check that the text is complete and that all figures, tables and their legends are included. Also check the accuracy of special characters, equations, and electronic supplementary material if applicable. If necessary refer to the Edited manuscript. • The publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…Several studies so far demonstrated that patients may stay stable after switching (for various reasons) from IFNbeta and GLAT to DMF and TERI [23][24][25][26][27][28]. In particular, Buron et al provided data from the Danish Multiple Sclerosis Registry showing that switching from injectables to DMF and TERI in clinically stable RRMS patients did not increase the risk of disability accumulation [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies so far demonstrated that patients may stay stable after switching (for various reasons) from IFNbeta and GLAT to DMF and TERI [23][24][25][26][27][28]. In particular, Buron et al provided data from the Danish Multiple Sclerosis Registry showing that switching from injectables to DMF and TERI in clinically stable RRMS patients did not increase the risk of disability accumulation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Most clinicians wish to resort to an evidence-based decision in the case of treatment switches. However, studies comparing the clinical effectiveness between a horizontal and vertical switch after a platform therapy [interferon beta (IFN-beta) or glatiramer-acetate (GLAT)] [16] provided conflicting results [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. These discrepancies ask for further investigations, especially based on real-life data.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were conducted in the following countries: France (3 articles) [20,26,30]; United States (3 articles) [18,28,31]; Italy (2 articles) [21,29]; Austria [23]; Denmark [22]; Germany [19]; Iran [27]; Sweden [24]; international registry [25].…”
Section: Search Ndingsmentioning
confidence: 99%
“…To deal with the lack of randomization, adjusted estimates were based on propensity score matching in six studies [19,24,25,[27][28][29]; multivariable regression in four studies [18,20,21,30]; inverse probability treatment weighting in three studies [22,23,26]; no correction in one studies without relevant betweenarm difference at baseline [31]. Six studies were funded by the manufacturer of DMF [18, 19,28] and TRF [24,30,31].…”
Section: Search Ndingsmentioning
confidence: 99%
“…Importantly, all published studies have found that oral DMTs are preferred over injectables [ 13 ]; better compliance and persistence have been reported in patients who were initially indicated for oral DMTs compared with injectables [ 14 , 15 ]. Teriflunomide is a once-daily oral DMT prescribed either as a first-line or as an alternative for patients with “needle fatigue” [ 16 ]. Of the oral DMTs, teriflunomide is likely to have a better persistence and adherence than dimethyl fumarate [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%